Graphene and its derivatives (GO, rGO and GQD): a comprehensive review of their role in combating COVID-19 - Spandan Guha; Shanta Chakrabarty (Advances in Physics: X)
The COVID-19 pandemic has ignited a search for innovative solutions to tackle viral transmission and ensure early detection. Graphene and its derivatives have emerged as promising materials in this fight, showcasing impressive potential across a diverse range of applications. From frontline defenses like antiviral PPE with enhanced filtration and breathability to microscopic detective work via highly sensitive FET biosensors, graphene offers a multifaceted attack on the SARS-CoV-2 virus. Its impact extends beyond diagnostics, empowering energy storage and disinfection technologies while revolutionizing drug delivery and air purification through virus-capturing filters. Antiviral coatings and vigilant nano-sensors further bolster its arsenal, offering comprehensive protection at the surface and microscopic levels. Moreover, graphene-based masks, with their potential to reduce air pollution exposure, may even offer an additional layer of protection against COVID-19 in polluted areas. In summary, graphene emerges as a versatile guardian against COVID-19, poised to revolutionize the fight against the pandemic and beyond. Its diverse applications, coupled with ongoing research, paint a compelling picture of a future where one atom at a time, graphene rewrites the narrative of viral defense.